Development of an Electronic Module to Improve Mathematical Representation in Two Variable Linear Equations - Hamdan Sugilar; Iyon Maryono; Wahyudin Wahyudin; Sani Insan Muhamadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
This study aims to develop an HTML5 Package-based E-Module on the material of Two-Variable Linear Equation System (SPLDV) which is valid and practical on, the results of the mathematical representation test of students solving SPLDV problems on 12 students obtained an average score of 75 in the good category. The research method used is Research and Development with a 4D development model, which includes the Define, Design, Develop, and Disseminate stages. Data collection techniques through media validation tests through media and material expert validation forms, mathematical representation tests, questionnaire distribution. Data analysis by calculating the percentage of media and material expert assessments, and calculating questionnaire responses and mathematical representation test scores. The results of the media expert review show that the validity of the e-module from the media and material aspects is very valid. The practicality test on a large scale shows a percentage of 78.91% which is classified as practical. Student responses to this module are very good. In addition, the test results for 12 students showed an average score of 75 for completing SPLDV questions, which is considered good. Overall, it was concluded that the developed HTML5 Package-based SPLDV e-Module met the criteria for validity, practicality, and effectiveness for use in learning.